Analysis of Halal Supply Chain Policy and Its Impact on Sharia Business and Economic Growth - Peristiwo, Hadi; Firdaus, Farhan; Haryati, Sri (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2024)
As the global Muslim population grows, the demand for halal goods and services is rising, necessitating a comprehensive strengthening of the halal value chain. This effort is crucial for enhancing the potential of Sharia-compliant businesses and the broader Islamic economy. This study seeks to evaluate the performance of key strategic entities involved in halal supply chain policies and to determine the significant impact of these policies on Sharia business and economic growth. Employing a literature review method, this research systematically searched published articles from 2010 to 2022 across databases such as Sage, Elsevier Science, and Taylor Francis. Keywords used included "halal supply chain," "Sharia business," and "Islamic economy." The findings reveal that the effectiveness of halal supply chain policies, including their formulation and implementation, plays a critical role in safeguarding the integrity and robustness of the halal supply chain, thereby significantly influencing the development of Sharia-compliant businesses and economic growth.